Snake Bite as a Public Health Problem: Bangladesh Perspective - Alam, ABM Saiful; Islam, AKM Monwarul; Jesmin, Humayra (BIRDEM Medical Journal, 2016)
Snake bite is an important but often under-recognized public health problem in Bangladesh, with an incidence density one of the highest in the world, which may be 623.4/100,000 person years. The proportion of poisonous snake bites is 10 to 45%, with the reported mortality 0.5 to 22%. Among the 82 species of snakes, 28 are venomous; bites by green pit vipers, cobras and kraits are the most commonly identified ones. High population density, widespread agricultural activities, numerous venomous snake species and lack of functional snake bite control programs favour the high burden of snake bites. Poorer rural populations are the main victims, imposing considerable socioeconomic impact. Treatment of snake bite is largely dominated by traditional snake charmers (Ozha) or Kaviraj offering unscientific practices and healers, causing undue delay and precluding standard medical management. Delayed presentation to the hospital, lack of availability of antivenom and modern management facility are the main causes of death. Antivenoms are entirely dependent on import, are expensive, and are not customized to local needs. Auxiliary intensive care facilities are not widely available; health care personnel often lack necessary expertise. However, the trend is changing. Public awareness is growing, health care personnel are being trained, and a national guideline for snake bite management has been formulated. Further research, introduction of modern diagnostic facilities, local manufacture of antivenom, and above all, integrated approach on the part of Government, policy-makers and international community can change the outlook of snake bite as a neglected tropical condition in Bangladesh. Birdem Med J 2015; 5(1): 24-29